2000
DOI: 10.1016/s0092-8674(00)80704-7
|View full text |Cite
|
Sign up to set email alerts
|

Implications for Chk1 Regulation: The 1.7 Å Crystal Structure of Human Cell Cycle Checkpoint Kinase Chk1

Abstract: The checkpoint kinase Chk1 is an important mediator of cell cycle arrest following DNA damage. The 1.7 A resolution crystal structures of the human Chk1 kinase domain and its binary complex with an ATP analog has revealed an identical open kinase conformation. The secondary structure and side chain interactions stabilize the activation loop of Chk1 and enable kinase activity without phosphorylation of the catalytic domain. Molecular modeling of the interaction of a Cdc25C peptide with Chk1 has uncovered severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(96 citation statements)
references
References 51 publications
(1 reference statement)
5
89
2
Order By: Relevance
“…It is possible that Crb2 and Claspin perform similar functions in their respective organisms. Interestingly, certain deletions or point mutations in the C terminus of Chk1 activate Chk1 when assayed with in vitro kinase assays or the Xenopus extract mitotic induction system (35)(36)(37). These findings suggest that the C terminus of Chk1 might inhibit Chk1 activity.…”
Section: Discussionmentioning
confidence: 97%
“…It is possible that Crb2 and Claspin perform similar functions in their respective organisms. Interestingly, certain deletions or point mutations in the C terminus of Chk1 activate Chk1 when assayed with in vitro kinase assays or the Xenopus extract mitotic induction system (35)(36)(37). These findings suggest that the C terminus of Chk1 might inhibit Chk1 activity.…”
Section: Discussionmentioning
confidence: 97%
“…However, the fact that CK2b interacts specifically with A-Raf (Boldyreff and Issinger, 1997) but not c-Raf (Chen et al, 1997;Hagemann et al, 1997), suggests that kinase interaction with CK2b may require higher specificity. The structure determination of the human Chk1 kinase (Chen et al, 2000) has indicated that the activity of the kinase domain (residues 1-265) of human Chk1 is over 20-fold more active than the full-length Chk1 kinase toward Cdc25C substrate. These data support the idea that the C-terminal region of Chk1 plays a negative role on Chk1 kinase activity.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of human Chk1 kinase domain fragment in binary complex with the ATP analog AMP-PNP has been solved (Chen et al, 2000). Based on this structure and that of the CK2 holoenzyme (Niefind et al, 2001), we have used computer modeling to examine the possible interaction between Chk1 and CK2b.…”
Section: Interaction With Chk1 Requires the C-terminal Tail Of Ck2bmentioning
confidence: 99%
“…In addition to the identification of Ser-123 as a target for Chk1 phosphorylation, the human Cdc25A protein sequence contains additional six serine residues that corresponds to the consensus Chk1 and Chk2 phosphorylation motif (Arg-X-X-Ser) (17). Among them are Ser-75, Ser-123, and Ser-177 ( Fig.…”
Section: Analysis Of Chk1 and Chk2 Phosphorylation Sites Inmentioning
confidence: 99%